Microbial circadian clocks: host-microbe interplay in diel cycles - Emily M. Wollmuth; Esther R. Angert (BMC Microbiology, 2023)
Abstract Background Circadian rhythms, observed across all domains of life, enable organisms to anticipate and prepare for diel changes in environmental conditions. In bacteria, a circadian clock mechanism has only been characterized in cyanobacteria to date. These clocks regulate cyclical patterns of gene expression and metabolism which contribute to the success of cyanobacteria in their natural environments. The potential impact of self-generated circadian rhythms in other bacterial and microbial populations has motivated extensive research to identify novel circadian clocks. Main text Daily oscillations in microbial community composition and function have been observed in ocean ecosystems and in symbioses. These oscillations are influenced by abiotic factors such as light and the availability of nutrients. In the ocean ecosystems and in some marine symbioses, oscillations are largely controlled by light-dark cycles. In gut systems, the influx of nutrients after host feeding drastically alters the composition and function of the gut microbiota. Conversely, the gut microbiota can influence the host circadian rhythm by a variety of mechanisms including through interacting with the host immune system. The intricate and complex relationship between the microbiota and their host makes it challenging to disentangle host behaviors from bacterial circadian rhythms and clock mechanisms that might govern the daily oscillations observed in these microbial populations. Conclusions While the ability to anticipate the cyclical behaviors of their host would likely be enhanced by a self-sustained circadian rhythm, more evidence and further studies are needed to confirm whether host-associated heterotrophic bacteria possess such systems. In addition, the mechanisms by which heterotrophic bacteria might respond to diel cycles in environmental conditions has yet to be uncovered.